DAYA TARIK PEMBERI-KERJA MENURUT PERSEPSI GENERASI X DAN Y - Tifani Onibala; Tria Rendi Manurun (Universitas Bunda Mulia, 2017)
This study attempts to identify the dimensions of employers’ attractivenes, to examine their perceived important levels.In order to respond to these questions, a field study is conducted and data is collected from a purposive of 169 respondents (employed and un-employed college students). Analysis results indicated that there are differences perceptions between X and Y generations. Generation X put higher expectations on the condition of the company, corporate image, training and development, job security, employment conditions, teamcohesion, leadership style, diversity, work schedule autonomy and decision-making autonomy, task variety & significance, flexible working environment. Y generation put higher expectation on the location of work, commitment/atmosphere, CSR, and the work environment.Keywords: employer attractiveness, generation X, generation Y